2016
DOI: 10.2147/idr.s96163
|View full text |Cite|
|
Sign up to set email alerts
|

Strategies for prevention of ultrasound-guided prostate biopsy infections

Abstract: Prostate cancer is the most common cancer in male patients and the second leading cause of cancer-related mortality in males. To confirm the diagnosis of prostate cancer, an ultrasound-guided needle biopsy is necessary to obtain prostate tissue sufficient for histologic analysis by pathologists. Ultrasound-guided prostate needle biopsy can be accomplished via a transperineal or transrectal approach. The latter biopsy technique involves placing an ultrasound probe into the rectum, visualizing the prostate locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Currently, transrectal ultrasound-guided prostate biopsy (TRUSPB) is the gold standard for obtaining pathological specimens to diagnose prostate cancer; 3 however, complications following TRUSPB vary widely and include hematuria, hematospermia, infection, pain, rectal bleeding, urinary retention, lower urinary tract symptoms, erectile dysfunction, and mortality. 4 It has been reported that minor complications such as bleeding and pain are frequent, 5 but worryingly, infectious complications that may lead to death have increased over time.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, transrectal ultrasound-guided prostate biopsy (TRUSPB) is the gold standard for obtaining pathological specimens to diagnose prostate cancer; 3 however, complications following TRUSPB vary widely and include hematuria, hematospermia, infection, pain, rectal bleeding, urinary retention, lower urinary tract symptoms, erectile dysfunction, and mortality. 4 It has been reported that minor complications such as bleeding and pain are frequent, 5 but worryingly, infectious complications that may lead to death have increased over time.…”
Section: Introductionmentioning
confidence: 99%
“…Culture-guided antimicrobial prophylaxis is a promising strategy to reduce the amount of TRUSP-related infectious complications (7,12,13). In this strategy, a prebiopsy rectal swab is obtained to screen for resistant rectal GNB in the rectum in patients undergoing TRUSP.…”
mentioning
confidence: 99%